2015
DOI: 10.1016/j.celrep.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of and Molecular Basis for SIRT6 Loss-of-Function Point Mutations in Cancer

Abstract: Chromatin factors have emerged as the most frequently affected family of proteins in cancer. We have previously identified the histone deacetylase SIRT6 as a key tumor suppressor, yet whether point mutations are selected for in cancer remains unclear. In this manuscript, we characterized naturally occurring patient-derived SIRT6 mutations. Strikingly, all the mutations significantly affected either stability or catalytic activity of SIRT6, indicating that these mutations were selected for in these tumors. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 21 publications
3
66
0
Order By: Relevance
“…Recently, SIRT6 mutations were found in several tumor types such as non-small-cell lung cancer, renal clear cell carcinoma, cervical carcinoma, and melanoma[19]. Since naturally occurring tumor-associated mutations in SIRT6 were shown to alter its stability, localization, and/or enzymatic activity[19], we checked SIRT6 status in HCC tissues and cell lines using several public databases such as COSMIC (Catalogue of Somatic Mutations in Cancer, http://cancer.sanger.ac.uk/cosmic) and Cancer Genome Atlas (https://tcga-data.nci.nih.gov/docs/publications/tcga/).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SIRT6 mutations were found in several tumor types such as non-small-cell lung cancer, renal clear cell carcinoma, cervical carcinoma, and melanoma[19]. Since naturally occurring tumor-associated mutations in SIRT6 were shown to alter its stability, localization, and/or enzymatic activity[19], we checked SIRT6 status in HCC tissues and cell lines using several public databases such as COSMIC (Catalogue of Somatic Mutations in Cancer, http://cancer.sanger.ac.uk/cosmic) and Cancer Genome Atlas (https://tcga-data.nci.nih.gov/docs/publications/tcga/).…”
Section: Resultsmentioning
confidence: 99%
“…Since naturally occurring tumor-associated mutations in SIRT6 were shown to alter its stability, localization, and/or enzymatic activity[19], we checked SIRT6 status in HCC tissues and cell lines using several public databases such as COSMIC (Catalogue of Somatic Mutations in Cancer, http://cancer.sanger.ac.uk/cosmic) and Cancer Genome Atlas (https://tcga-data.nci.nih.gov/docs/publications/tcga/). Regarding HCC cell lines used for our experiments, mutation status of SK-Hep1 Huh-7, SNU475 and SNU449 could be obtained from COSMIC.…”
Section: Resultsmentioning
confidence: 99%
“…No significant levels of SIRT6 could be detected at the STAT3 target promoters over the time course of metabolic stress in HepG2 control, SIRT6kd, or SIRT6/PKM2 doubleknockdown cells. We also examined the effect of PKM2 on SIRT6-mediated regulation of previously described SIRT6 target genes (4,7,10). We observed that wild-type PKM2 and the constitutively nuclear PKM2 K433Q mutant had no effect on SIRT6 occupancy at the promoters of known SIRT6 target genes (Fig.…”
Section: H133ymentioning
confidence: 92%
“…Elevated c-JUN levels in hepatocellular carcinoma down-regulate SIRT6 expression in a c-FOS-dependent manner (8). Recently, naturally occurring cancer-associated point mutations were identified in SIRT6 that result in its loss of tumor-suppressor functions (10). However, the role of SIRT6 enzymatic activities in its tumorsuppressor functions is not well understood.…”
mentioning
confidence: 99%
“…Interestingly, Sirt6 has very low in-vitro histone deacetylase activity but is activated up to 35-fold by select long-chain fatty acids (LCFAs), including myristic, oleic, and linoleic acid (95). Sirt6 plays a role in genome stability and glucose homeostasis, and loss of Sirt6 function plays a role in the metabolic switch that occurs in human tumors (102,103). …”
Section: Regulation Of Chromatin Modification By Endogenous Metabolitmentioning
confidence: 99%